2021
DOI: 10.1093/ajcn/nqaa272
|View full text |Cite
|
Sign up to set email alerts
|

Associations of human milk oligosaccharides and bioactive proteins with infant growth and development among Malawian mother-infant dyads

Abstract: Background Human milk oligosaccharides (HMOs) and bioactive breast milk proteins have many beneficial properties. Information is sparse regarding associations between these milk constituents and infant growth and development in lower-income countries. Objectives We aimed to examine associations of milk content of HMOs and bioactive proteins at 6 mo postpartum with infant growth and motor and cognitive development. These are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(87 citation statements)
references
References 46 publications
3
68
2
Order By: Relevance
“…In general, current evidence on HMO in relation to infant growth is inconclusive, with substantial variations being observed across geographic locations. [26][27][28][29] Interestingly, however, two studies reported negative association between 6'SL content and infant growth, which is in agreement with our results. [27,28] It has been proposed that those variations may be partly due to the differing composition of gut microbiota as HMO might interact differently according to the intestine microbiome profile.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In general, current evidence on HMO in relation to infant growth is inconclusive, with substantial variations being observed across geographic locations. [26][27][28][29] Interestingly, however, two studies reported negative association between 6'SL content and infant growth, which is in agreement with our results. [27,28] It has been proposed that those variations may be partly due to the differing composition of gut microbiota as HMO might interact differently according to the intestine microbiome profile.…”
Section: Discussionsupporting
confidence: 93%
“…[26][27][28][29] Interestingly, however, two studies reported negative association between 6'SL content and infant growth, which is in agreement with our results. [27,28] It has been proposed that those variations may be partly due to the differing composition of gut microbiota as HMO might interact differently according to the intestine microbiome profile. [28] Future studies are needed to take microbiota profile into account when exploring association between HMO content and infant growth.…”
Section: Discussionsupporting
confidence: 93%
“…There were several significant associations of the bioactive breast milk proteins with the other bioactive proteins, groups of HMOs, or individual HMOs ( Supplemental Table 1 ) as described previously ( 22 ).…”
Section: Resultsmentioning
confidence: 86%
“…All statistical analyses were performed using SAS version 9.4 (SAS Institute Inc.). We first examined whether median values of HMOs and proteins differed between women with the secretor phenotype [positive for the functional enzyme encoded by the fucosyltransferase 2 ( FUT2 ) gene, as determined by >6% α1-2-linked fucosylated HMOs, as described previously ( 22 )] and nonsecretors using the nonparametric Kruskal–Wallis test. Covariate adjusted regression models were examined separately in secretors and in nonsecretors for those HMOs that differed between secretors and nonsecretors, and also when the interaction between secretor status and the predictor variable was significant.…”
Section: Methodsmentioning
confidence: 99%
“…α-lactalbumin is the predominant whey protein in HM. The concentrations of α-lactalbumin in milk from different populations have been reported, including Switzerland [ 9 ], the United States [ 19 ], Malawi [ 42 ], and China [ 13 , 36 ]. The present study found the concentration of α-lactalbumin remained relatively consistent in the first two weeks of lactation and then decreased slightly in the first month postpartum.…”
Section: Discussionmentioning
confidence: 99%